E-Marketing Jaya Abadi Computer (JAC) - Honni Honni; Raymond Raymond; Johni Johni; Wendi Tan (ComTech: Computer, Mathematics and Engineering Applications, 2011)
Internet has been widely used by manufacturers and distributors to expand product markets for its advantageous in quick process, practicality and low cost. Jaya Abadi Computer (JAC) as a sales distributor and service agent of computer equipment still perform its direct marketing manually on the spot, so that the marketing only reaches a small scope. This article analyzes the market opportunity of JAC; determines the marketing strategy and builds e-marketing website for JAC based on customer experience using The Seven Stage Cycle of Internet Marketing. The results obtained are an e-marketing website to support the marketing activities of JAC. Eventually it can be concluded that by building an e-marketing, JAC can reach as well as expand market opportunities in virtual world, use the right marketing strategy, and meet customer needs through features on the website.